Acute Complications Associated With Haemodialysis in a CKD Cohort Population - Rathinavelu, Mohanraj; Gari, Anusha Hanumaih; Uppara, Veerendra; Alshamiri, Farooq A; Sandyapakula, Balaiah; Thomas, Bijoy (Indian Journal of Pharmacy Practice)
Background: Chronic kidney disease is becoming a major public health problem worldwide. The expansion of haemodialysis into a chronic renal replacement therapy also created a new field of medical science, sometimes termed the physiology of the artificial kidney but associated with acute complications. Objectives: The current longitudinal cohort study of six months duration was performed in a tertiary care teaching hospital of south India to assess acute complications associated with haemodialysis in a CKD cohort. Materials and Methods: A Structured process was followed for obtaining permission from hospital authority after the acceptance of institutional review board, a total of 109 patients diagnosed with CKD of both the genders attending department of nephrology for haemodialysis showing willingness towards the study were included and others were excluded. Enrolled patient’s demography, approximate data of diagnosis (old cases) and definite data of diagnosis (new cases), vital parameters, treatment, physical examinations and laboratory parameters were obtained and documented. Results: In our study of 109 CKD patients, 81.65% were male and 49.53% falls under the age group of 41 – 60 years, it was observed that 56.88% patients suffers severe anaemia out of which 43.12% were female, and 51.37% suffered severe chronic kidney disease based on serum creatinine levels. Stage I hypertension was reported in 36.69% of patients. Conclusion: In conclusion, complications caused by the reasons other than the dialysis machine and water system remain as a significant cause of morbidity and mortality in haemodialysis patients.
Keywords: Acute complications; end stage renal disease; haemodialysis; serum creatinine level; cohort study